2014
DOI: 10.11646/zootaxa.3784.3.5
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Anacanthoroides and redescription of Apedunculata discoidea (Monogenoidea) parasitizing Prochilodus argenteus (Actinopterygii) from the São Francisco River, Brazil

Abstract: Anacanthoroides sanctifrancisci n. sp. from the gills of 'curimatã-pacú', Prochilodus argenteus from the São Francisco River, Brazil, is described and illustrated. Anacanthoroides, monotypic, is represented by Anacanthoroides mizellei. The new species can be distinguished from A. mizellei by the presence of a pair of muscular pseudosuckers in the anterior region of the body, an accessory piece not articulated to the male copulatory organ and the number of rings in the male copulaty complex. Apedunculata discoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Pseudacolpenteron Bychowsky & Gussev, 1955) (see [20]); Anacanthorus (Mizelle & Price 1965) Kritsky et al 1992; Anacanthoroides Kritsky & Thatcher 1976; Anonchohaptor (Mueller 1938) Kritsky, Leiby & Shelton, 1972; Icelanonchohaptor Leiby, Kritsky & Peterson, 1972; Kritskyia (Kohn 1990) Boeger et al [2]; Octouncuhaptor Mendoza-Franco, Roche & Torchin, 2008; Pavanelliella (Kritsky & Boeger, 1988) Kritsky & Mendoza-Franco, 2003; and Telethecium Kritsky, Every & Boeger, 1996, all from characiform, perciform, clupeiform, cypriniform and siluriform fishes], with that of the dactylogyrid found in the urinary bladder of S. hubbsi (Beloniformes), we concluded that it is a new dactylogyrid that does not fit into any genera listed above (see [2, 17–19, 21–23, 26, 30, 32]). Therefore, Paracolpenteron n. gen. is proposed to accommodate the new species.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Pseudacolpenteron Bychowsky & Gussev, 1955) (see [20]); Anacanthorus (Mizelle & Price 1965) Kritsky et al 1992; Anacanthoroides Kritsky & Thatcher 1976; Anonchohaptor (Mueller 1938) Kritsky, Leiby & Shelton, 1972; Icelanonchohaptor Leiby, Kritsky & Peterson, 1972; Kritskyia (Kohn 1990) Boeger et al [2]; Octouncuhaptor Mendoza-Franco, Roche & Torchin, 2008; Pavanelliella (Kritsky & Boeger, 1988) Kritsky & Mendoza-Franco, 2003; and Telethecium Kritsky, Every & Boeger, 1996, all from characiform, perciform, clupeiform, cypriniform and siluriform fishes], with that of the dactylogyrid found in the urinary bladder of S. hubbsi (Beloniformes), we concluded that it is a new dactylogyrid that does not fit into any genera listed above (see [2, 17–19, 21–23, 26, 30, 32]). Therefore, Paracolpenteron n. gen. is proposed to accommodate the new species.…”
Section: Resultsmentioning
confidence: 86%
“…A. chiapanensis n. sp. differs from X. xenentodoni in having slightly overlapping gonads (tandem in X. xenentodoni ); a twisted MCO (coiled tube in X. xenentodoni ); an unarticulated accessory piece and MCO (accessory piece articulated with the base of the MCO in X. xenentodoni ); by lacking anchor roots connected by a threadlike sclerotized piece (present in X. xenentodoni ); hooks with a shank composed of two subunits (present in X. xenentodoni ); and tegument transversally striated ventrally at the region of the copulatory complex (present in X. xenentodoni ) (see [15, 30]).…”
Section: Resultsmentioning
confidence: 99%